Rancang Bangun (SISMAKAR) Sistem Informasi Surat Masuk dan Keluar Berbasis Web - Sandro Alfeno; Arsa Kumar; A. Fachrul Rozy Saleh (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
An organization, be it a company or a government, expects its goals to be achieved with optimal results by implementing the best service, one of which is in the administration department. One of the services provided is correspondence management, this is a very important service in maintaining information. between companies or governments, this service should be carried out effectively which is the main focus, in the Pasar Baru kelurahan, Tangerang City continues to strive for the best service in terms of managing incoming and outgoing mail, but in Pasar Baru kelurahan it is still not entirely computerized and still uses manual recording , with this background the author analyzes the best and appropriate solution to overcome it by creating an information system for managing incoming and outgoing mail. ng accurate, precise and efficient.